2007
DOI: 10.1038/sj.bjc.6603521
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent irinotecan, oxaliplatin and UFT in first-line treatment of metastatic colorectal cancer: a Phase I study

Abstract: The feasibility of combining UFT plus leucovorin (LV) with alternating irinotecan and oxaliplatin was investigated in the first-line treatment of patients with advanced colorectal cancer. Twenty-five patients, median age 63 (range 24 -79) years, World Health Organisation performance status 0 -2 and median four marker lesions, received irinotecan 180 mg m À2 on day 1, oxaliplatin 85 -100 mg m À2 on day 15 and UFT 200 -300 mg m À2 day À1 with LV 90 mg day À1 , days 1 -21 of a 28-day cycle. Patients were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In that study, an ORR of 58.5%, median overall survival of 17.3 months and median TTP of 8.8 months were reported. Similarly, Sheikh et al reported promising results in a phase I study of alternating UFT -oxaliplatin and UFT -irinotecan in the first-line treatment of patients with mCRC (Sheikh et al, 2007). A response rate of 71% was reported in 25 patients, with a median TTP of 8.8 months.…”
Section: Discussionmentioning
confidence: 91%
“…In that study, an ORR of 58.5%, median overall survival of 17.3 months and median TTP of 8.8 months were reported. Similarly, Sheikh et al reported promising results in a phase I study of alternating UFT -oxaliplatin and UFT -irinotecan in the first-line treatment of patients with mCRC (Sheikh et al, 2007). A response rate of 71% was reported in 25 patients, with a median TTP of 8.8 months.…”
Section: Discussionmentioning
confidence: 91%
“…The use of triple associations with irinotecan, oxaliplatin and 5-FU-LV further increased the efficacy of systemic chemotherapy. Response rates as high as 70% were obtained in 3 different studies and the overall median survival improved to 26 months [3,4,5]. The more recent development of 2 monoclonal antibodies, cetuximab (Erbitux®), a monoclonal antibody against the epidermal growth factor receptor, and bevacizumab (Avastin®), a humanized antibody against the vascular endothelial growth factor [6, 7], has improved the response rates even further.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that alternating oxaliplatin and irinotecan would allow patients to benefit from concurrent treatment with all three drugs as soon as they were diagnosed with metastatic disease, while allowing them to recover from adverse events associated with each drug before it was administered again. Results from the phase I study have been published in full (Sheikh et al, 2007). Here we present results for the expanded group of patients treated at the maximum tolerated dose (MTD) and overall results from the phase I/II study.…”
mentioning
confidence: 91%
“…Inclusion and exclusion criteria have been described previously (Sheikh et al, 2007). In brief, patients were aged X18 years, had no prior chemotherapy for metastatic disease and a World Health Organization performance status of 0 -2.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation